OPTIMIZATION OF AKIDAH AKHLAK LEARNING STRATEGIES THROUGH THE APPLICATION OF MIND MAPPING METHOD AT MTsN 2 MEDAN - Nasution, Ananda Sholih; Zulham (Pena Cendekia Insani, 2025)
The teacher-centered learning (TCL) model remains a common issue encountered in the process of Islamic Education learning, including the subject of Akidah Akhlak. Ideally, with the implementation of the 2013 Curriculum, the student-centered learning (SCL) approach should have been advocated, but it has not been fully realized. Therefore, this research aims to delve deeper into the application of the SCL approach in Akidah Akhlak learning, specifically utilizing the mind mapping method to achieve active learning as expected by the Merdeka Curriculum. This qualitative case study research employs data collection techniques such as observation, interviews, and documentation. Data analysis techniques involve data condensation, data presentation, and concluding with a summary. Additionally, data validity techniques include prolonged engagement and triangulation of data sources, methodologies, and time. The results of this study indicate that the application of the mind mapping method implemented in the eighth grade at MTsN 2 Medan is effective in enhancing understanding, creativity, collaboration, and making Akidah Akhlak learning more enjoyable for students.